A randomized controlled trial of a brief online intervention to reduce alcohol consumption in new university students: Combining self‐affirmation, theory of planned behaviour messages, and implementation intentions. Issue 1 (20th September 2017) - Norman, Paul; Cameron, David; Epton, Tracy; Webb, Thomas L.; Harris, Peter R.; Millings, Abigail; Sheeran, Paschal
Abstract : Objectives: Excessive alcohol consumption increases when students enter university. This study tests whether combining (1) messages that target key beliefs from the theory of planned behaviour (TPB) that underlie binge drinking, (2) a self‐affirmation manipulation to reduce defensive processing, and (3) implementation intentions (if‐then plans to avoid binge drinking) reduces alcohol consumption in the first 6 months at university. Design: A 2 (self‐affirmation) × 2 (TPB messages) × 2 (implementation intention) between‐participants randomized controlled trial with 6‐month follow‐up. Methods: Before starting university, students ( N  =   2, 951) completed measures of alcohol consumption and were randomly assigned to condition in a full‐factorial design. TPB cognitions about binge drinking were assessed immediately post‐intervention ( n  =   2, 682). Alcohol consumption was assessed after 1 week ( n  =   1, 885), 1 month ( n  =   1, 389), and 6 months ( n  =   892) at university. TPB cognitions were assessed again at 1 and 6 months. Results: Participants who received the TPB messages had significantly less favourable cognitions about binge drinking (except perceived control), consumed fewer units of alcohol, engaged in binge drinking less frequently, and had less harmful patterns of alcohol consumption during their first 6 months at university. The other main effects were non‐significant. Conclusions: The findings support the use of TPB‐based interventions to reduce students' alcohol consumption, but question the use of self‐affirmation and implementation intentions before starting university when the messages may not represent a threat to self‐identity and when students may have limited knowledge and experience of the pressures to drink alcohol at university. Statement of contribution What is already known on this subject? Alcohol consumption increases when young people enter university. Significant life transitions represent potential teachable moments to change behaviour. Interventions with a strong theoretical basis have been found to be more effective. What does this study add? A brief online intervention delivered to students before they start university can reduce alcohol consumption. The theory of planned behaviour can be used to inform the design of interventions to change health behaviour.